2013
DOI: 10.1108/17595901311299008
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and sociological resilience in megacities context

Abstract: Purpose -During the last few decades social resilience and social vulnerability have been two crucial sociological concepts for everyone involved in crisis and disaster management. The fundamental purpose in the present analysis is based on the consideration of resilience from a sociological perspective and the notion of social capital, its proper features, dynamics and processes within different groups of people involved in a disaster process. Design/methodology/approach -All these social components could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…This descriptive expansion moves the concept more towards the social sciences and philosophy (e.g. Lucini, 2013) with the normative consequence that it has to deal with 'equity', 'power', 'justice' and 'social capital', thus increasing complexity. Geography continues to provide a solid grounding of theory in reality while linking ecology and society (see also Cote and Nightingale, 2012).…”
Section: Resilience In Theory: Concepts and Characteristicsmentioning
confidence: 99%
“…This descriptive expansion moves the concept more towards the social sciences and philosophy (e.g. Lucini, 2013) with the normative consequence that it has to deal with 'equity', 'power', 'justice' and 'social capital', thus increasing complexity. Geography continues to provide a solid grounding of theory in reality while linking ecology and society (see also Cote and Nightingale, 2012).…”
Section: Resilience In Theory: Concepts and Characteristicsmentioning
confidence: 99%
“…Conversely, qualitative approaches are able to frame the representation of social processes (Bailey et al, 1999) and to grasp complexity in DR as a social construct (Hutter et al, 2011;Kuhlicke, 2013;Weichselgartner & Kelman, 2014). Qualitative methodologies can collect data related to the political 'embeddedness' of resilience (Raco & Street, 2012), individual and community perceptions (Amundsen, 2012;Kuhlicke, 2013;Lucini, 2013Lucini, , 2014 and power relations (Cannon & Müller-Mahn, 2010;Lorenz, 2013). Interviews are part of a larger set of qualitative methodologies in social sciences (Crang, 2002) that add evidence to archival research (Secor, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Scholars (e.g., Kenis et al 2009;Lundin and Söderholm 1995) have suggested that social relations and human interaction can be crucial to project management; often, the real challenge in disaster management projects is understanding the specific nature of social relations, structures, and processes (Lucini 2013). One aspect of social relations that is applicable to our context is the role of community groups.…”
Section: Community Group Processesmentioning
confidence: 99%